ANALISIS BIAYA PROYEK PENAMBAHAN LAYANAN PADA CALL CENTER YANG MELAYANI DELIVERY ORDER DI PT XYZ - Zuraida, Rida (Industrial and Systems Engineering Assessment Journal (INASEA), 2011)
Call center service is a separated business unit in PT XYZ, a fast food industry company,Â which served product information and delivery order. Regarding this business unit is also the profitÂ center, so the usage of call center service as outbound call seems to help increasing companyâsÂ profit. The research is done to see the function of new service in cost and estimated probable profit.Â The probable profit is based on payback period and rate of return of the additional project service.Â The result showed that there are 95.039 calls in a month that means about 9.504 data could beÂ used for telesales, plus 2.851 additinal continuous calls. From the total calls in a month need to beÂ invested to add position and additional telecommunication equipment for 10 positions. Based onÂ the cost analysis and estimated earnings, payback period from this period is about 1 year 7 monthsÂ in the amount of RoR for 3 years according to position level age as 53,7%.